Utilization of Solar Energy for Irrigation Pumps in Umbulrejo Village, Ponjong District, Gunungkidul Regency, Special Region of Yogyakarta: Pemanfaatan Energi Matahari Untuk Pompa Irigasi di Desa Umbulrejo, Kecamatan Ponjong, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta - Sentot Purboseno; Gani Supriyanto; Hermantoro Hermantoro; Nuraeni Dwi Dharmawati; Ruseno Adi (Yayasan Ahmar Cendekia Indonesia, 2023)
Farmers in Umbulrejo Village in Gunungkidul Regency, Yogyakarta are facing difficulties pumping water for their agriculture due to low electrical power availability. One alternative is to use solar-powered pumps, but this causes environmental problems and higher production costs. The Faculty of Agricultural Technology INSTIPER Yogyakarta is working with PT. Virama Karya to introduce the Clean Water and Irrigation Program for Umbulrejo Village Farmers, which includes planning, construction, operation, and monitoring of a ground water irrigation system with solar-powered pumps. The program's implementation is planned for 4 years and will include the construction of wells, water tanks, solar power plants, irrigation networks, and maintenance of the system. After 4 years, the village will own the system with guidance from the Stiper Agricultural Institute of Yogyakarta. Abstrak Petani di Desa Umbulrejo di Kabupaten Gunungkidul, Yogyakarta mengalami kesulitan memompa air untuk budidaya pertanian mereka karena ketersediaan tenaga listrik yang rendah. Salah satu alternatifnya adalah menggunakan pompa berbahan bakar solar, tetapi ini menimbulkan masalah lingkungan dan biaya produksi yang lebih tinggi. Fakultas Teknologi Pertanian INSTIPER Yogyakarta bekerja sama dengan Persero PT. Virama Karya untuk memperkenalkan program Penyediaan Air Bersih dan Air Irigasi untuk Petani Desa Umbulrejo yang mencakup perencanaan, pembangunan, operasional, dan monitoring sistem irigasi air tanah dengan pompa air tenaga surya. Pelaksanaan program direncanakan untuk 4 tahun dan akan mencakup pembangunan sumur, tandon air, pembangkit listrik tenaga surya, jaringan irigasi, dan pemeliharaan sistem. Desa akan menjadi pemilik sistem setelah 4 tahun dengan pendampingan dari Institut Pertanian Stiper Yogyakarta.